2022
DOI: 10.3389/fimmu.2022.867516
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps (NETs) Promote Non-Small Cell Lung Cancer Metastasis by Suppressing lncRNA MIR503HG to Activate the NF-κB/NLRP3 Inflammasome Pathway

Abstract: Neutrophil extracellular traps (NETs) that are produced in the tumour microenvironment (TME) have been suggested to play an essential role in the dissemination of metastatic cancer under multiple infectious and inflammatory conditions. However, the functions of NETs in promoting non-small cell lung cancer (NSCLC) metastasis and the underlying mechanisms remain incompletely understood. Here, we found that NETs promoted NSCLC cell invasion and migration by inducing epithelial to mesenchymal transition (EMT). To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 70 publications
2
26
0
Order By: Relevance
“…Active caspase-1 cleaves pro-IL-1b into mature and biologically active IL-1b, which is a potent proinflammatory mediator (Moretti and Blander, 2021). PMA-induced NETs have been shown to upregulate NLRP3 and IL-1b levels via a NF-kB signaling pathway in the tumour microenvironment in vitro (Wang et al, 2022). In this present study, it was confirmed that NETs further up-regulated NLRP3 and IL-1b expression in a high glucose inflammatory condition.…”
Section: Discussionsupporting
confidence: 81%
“…Active caspase-1 cleaves pro-IL-1b into mature and biologically active IL-1b, which is a potent proinflammatory mediator (Moretti and Blander, 2021). PMA-induced NETs have been shown to upregulate NLRP3 and IL-1b levels via a NF-kB signaling pathway in the tumour microenvironment in vitro (Wang et al, 2022). In this present study, it was confirmed that NETs further up-regulated NLRP3 and IL-1b expression in a high glucose inflammatory condition.…”
Section: Discussionsupporting
confidence: 81%
“…Functionally, NETs function as a physical barrier to shield tumor cells from interactions with neighboring anti-tumor immune cells such as NK cells and CD8 + T cells in the tumor immune microenvironment (TME), affecting the tumor immune landscape and tumor response to immunotherapy ( Ireland and Oliver, 2020 ; Teijeira et al, 2020 ). LncRNAs, as particular type of non-coding RNAs, have been reported to mediate NETs-induced cancer cell metastasis in the TME ( Wang et al, 2022 ). Therefore, the exploration of the relevance of the model based on NETs-related lncRNAs and the immune microenvironment of BC patients is essential.…”
Section: Discussionmentioning
confidence: 99%
“…The long non-coding RNAs (lncRNAs), non-coding RNA longer than 200 nucleotides, do not directly participate in protein coding in cells, but are engaged in vital biological regulatory processes, including transcriptional regulation, mRNA processing regulation and mRNA post-transcriptional regulation ( Yang et al, 2022 ). Recent finding indicated a role of lncRNA in regulating NETs in lung cancer ( Wang et al, 2022 ). However, the lncRNAs associated with NETs in BC are less studied, and most lncRNAs regulating NETs have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…While lncRNA-BACE1-AS is an immune-related factor in the tumorigenesis of melamona, its expression levels are negatively correlated with the neutrophil content ( 108 ). Neutrophil extracellular traps (NETs) generated in the tumor microenvironment promote the EMT process and metastasis by promoting the expression of lncRNA-MIR503HG and activating the downstream NF-κB/NLRP3 signaling pathway ( 109 ). Therefore, lncRNAs play an important role in the regulation of the immune microenvironment, thus affecting tumor progression.…”
Section: Lncrnas In the Immune Microenvironmentmentioning
confidence: 99%